2022
DOI: 10.1177/17562848221102283
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IL12/23 in ulcerative colitis: update on the role of ustekinumab

Abstract: As our comprehension of the pathogenic mechanisms of inflammatory bowel disease (IBD) increases, the therapeutic armamentarium for its treatment can expand, and novel target therapies join the treatment pipeline. Interleukin (IL)-12 and IL23 are two key cytokines responsible for promoting and perpetuating bowel inflammation in IBD. Ustekinumab is a monoclonal antibody directed against the shared p40 subunit of both cytokines, and it was recently approved for the treatment of ulcerative colitis (UC). In the piv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Pharmacokinetic analysis demonstrated that serum ustekinumab concentrations (SUCs) were proportional to dose and were not affected by concomitant immunomodulatory agents or prior exposure to biologic therapy [17]. RCTs and real-world studies with ustekinumab found Ustekinumab could potentially exhibit several advantages over other competitors in UC (anti-TNF-α drugs, vedolizumab, and tofacitinib), including a favorable profile of safety, effectiveness on certain extraintestinal manifestations, and a convenient administration mode [45]. These results suggest that Ustekinumab may be a safe and efficacious therapeutic agent for UC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic analysis demonstrated that serum ustekinumab concentrations (SUCs) were proportional to dose and were not affected by concomitant immunomodulatory agents or prior exposure to biologic therapy [17]. RCTs and real-world studies with ustekinumab found Ustekinumab could potentially exhibit several advantages over other competitors in UC (anti-TNF-α drugs, vedolizumab, and tofacitinib), including a favorable profile of safety, effectiveness on certain extraintestinal manifestations, and a convenient administration mode [45]. These results suggest that Ustekinumab may be a safe and efficacious therapeutic agent for UC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Widely used treatments for IBD, such as TNF‐α antagonists, have been ineffective and even detrimental in CGD patients presenting with IBD suggesting that CGD‐associated IBD may be mediated by different signalling molecules than classic idiopathic IBD. IL‐23 signalling in IBD patients has been demonstrated via higher serum levels of IL‐23 and increased mucosal transcription that leads to increased levels in IBD associated with CGD 63,64,66 . Ustekinumab, an IL‐12 and IL‐23 antagonist, has been successfully utilized in IBD cases in patients with CGD and might be the agent of choice for PG in CGD patients.…”
Section: Methodsmentioning
confidence: 99%
“…IL-23 signalling in IBD patients has been demonstrated via higher serum levels of IL-23 and increased mucosal transcription that leads to increased levels in IBD associated with CGD. 63,64,66 Ustekinumab, an IL-12 and IL-23 antagonist, has been successfully utilized in IBD cases in patients with CGD and might be the agent of choice for PG in CGD patients.…”
Section: Chronic Granulomatous Diseasementioning
confidence: 99%
“…[ 135 ] Among these drugs, Ustekinumab (UST), an antibody targets p40 subunit of both cytokines IL‐12 and IL23, has been clinically approved to be effective in moderate to severe UC treatment, and the results from a large phase III trial are expected soon. [ 136 ] Compared to the widely used placebo, Ustekinumab shows superior clinical and endoscopic outcomes with a favorable safety profile in IBD patients by either intravenous or subcutaneous injection. [ 137,138 ] Therefore, besides TNF‐ α , targeting IL­12/IL­23 or IL­23/IL­17 would also provide novel therapeutic strategy for IBD treatment.…”
Section: Advanced Nanomedicines Treat Ibd Through Different Therapeut...mentioning
confidence: 99%